Constant and variable amplitude fatigue testing of aluminum alloy 2024-T351 with ultrasonic and servo-hydraulic equipment. (October 2016) - Fitzka, M.; Mayer, H.
Highlights: Variable amplitude tests with servo-hydraulic and ultrasonic equipment are compared. Cycling frequency does not affect fatigue lifetime of 2024-T351 aluminum alloy. HCF cracks initiate at secondary phase surface particles at both frequencies. Influence of block length on HCF lifetime in variable amplitude tests is studied. Variable amplitude lifetimes decrease with decreasing block length. Abstract: Constant amplitude (CA) and variable amplitude (VA) fatigue lifetimes of the aluminum alloy 2024-T351 were measured with servo-hydraulic (8–70 Hz) and ultrasonic testing equipment (20 kHz) at positive load ratios. Experiments in the high cycle fatigue regime served to identify influences of frequency and testing method on lifetimes. CA tests showed similar numbers of cycles to failure for both methods. Ultrasonic tests were performed in pulsed mode. In ultrasonic VA tests vibration amplitude of successive pulses of 2000 cycles length is varied. Servo-hydraulic VA tests are performed by varying the load of successive blocks. Servo-hydraulic VA tests with block length 2000 cycles delivered lifetimes similar to the ultrasonic tests. No frequency effect is found in CA and VA tests. Cracks are preferentially initiated at secondary phase particles at both frequencies. Lifetimes in servo-hydraulic VA tests are reduced when block length is decreased from 2000 to 200, 20 and single load cycles. Varying the load for each successive cycle at 50 Hz is realized with a feed-forward optimization of control parameters. Lifetimes differ by a factor 6 for different block lengths indicating a strong load sequence effect.